2012
DOI: 10.3856/vol40-issue1-fulltext-21
|View full text |Cite
|
Sign up to set email alerts
|

Ostrea puelchana (D Orbigny 1842): a new host of Tumidotheres maculatus (Say, 1818) in northern Patagonia, Argentina

Abstract: ABSTRACT. Tumidotheres maculatus has been reported as a commensal of Mytilus platensis and Atrina seminuda and suggested as a parasite of Aequipecten tehuelchus in San Matías Gulf (SMG). The native flat oyster, Ostrea puelchana, has been studied in SMG for decades, and no crab-oyster association has been reported. In autumn-spring 2009 and 2010, oysters were collected from four banks in SMG, and the occurrence of T. maculatus inside the pallial cavity of O. puelchana was recorded. The prevalence varied between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…as observed in C. exasperatus) (Lima et al, 2017) and in E. gonagra (present study). In the same way, the species of O. puelchana can be host from many others decapods as observed by Martins and D'lncao (1996), which analyzed the presence of the pea crab Z. ostreum as endosymbiont of O. puelchana, while Doldan et al (2012) reported from the same ostreid host species the endosymbiont Tumidotheres maculatus (Say, 1818). Thus, here in we observed the opportunistic fixation observed by O. puelchana on the new basibiont E. gonagra from Brazilian coast.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…as observed in C. exasperatus) (Lima et al, 2017) and in E. gonagra (present study). In the same way, the species of O. puelchana can be host from many others decapods as observed by Martins and D'lncao (1996), which analyzed the presence of the pea crab Z. ostreum as endosymbiont of O. puelchana, while Doldan et al (2012) reported from the same ostreid host species the endosymbiont Tumidotheres maculatus (Say, 1818). Thus, here in we observed the opportunistic fixation observed by O. puelchana on the new basibiont E. gonagra from Brazilian coast.…”
Section: Introductionmentioning
confidence: 79%
“…The use of the hard substrate by the ostreid species O. puelchana, especially the use of the carapaces of the brachyuran crabs for the fixation, can be an advantage for the geographic distribution of the oyster along the Brazilian and Argentine provinces, due to wide mobility provided by these individuals from different coastal regions, which allows the occurrence of this species on a wide range of hosts (basibionts) (Doldan et al, 2012;Lima et al, 2017). The associations of O. puelchana with many crustaceans in the natural environment can be observed in different levels of occupation, as the use of crustacean as basibiont (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1 Introduction pibiosis is the main mechanism used by marine benthic sessile organisms in search of settlement for their development on hard substrates (ABELLÓ et al, 1990;NEGREIROS-FRANSOZO et al, 1995;EMPARANZA et al 2011). For the attachment in hard bottoms, the individuals present a wide range of morphological and behavioral adaptations, enabling survival in the aquatic environment (WAHL, 2008;DOLDAN et al, 2012). However, in aquatic habitats, hard substrate is limited or it exhibits high competition for space, especially in estuarine and coastal areas, where soft sediments and high levels of sedimentation are common (WAHL, 2008;LIMA et al, 2017).…”
mentioning
confidence: 99%